A potencialização do jogo Jenga para o ensino da matemática: Geojenga - Albieri, Cristiane Janasi (Universidade Federal de São Carlos, 2026)
This dissertation analyzes the relevance of playful activities, such as games, in the educational process, understanding them as fundamental tools for the construction of mathematical knowledge and demonstrating greater student engagement. It highlights the Mathematics Teaching Laboratory (LEM) as the primary physical and institutional space for the conception, development, and execution of these playful practices.The study presents the process of creating and implementing the LEM within the school environment, emphasizing its role as a pedagogical innovation that integrates theory and practice.The central focus of this work is geometry, which led to the development of the game GeoJenga—an adaptation and enhancement of the traditional game Jenga, specifically designed for teaching geometry.In addition to addressing plane and spatial geometry, the study illustrates a transition from geometry to arithmetic and algebra by exploring patterns, ultimately leading to the topic of Arithmetic Progression (AP).
Leveraging the Jenga game for mathematics education: Geojenga
Keywords: GeoJenga; Laboratório de Ensino de Matemática; Ensino lúdico de Matemática.; CIENCIAS EXATAS E DA TERRA::MATEMATICA; 4. Educação de Qualidade